Exosomal miR-125b Exerts Anti-Metastatic Properties and Predicts Early Metastasis of Hepatocellular Carcinoma - Kim, Hye Seon; Kim, Jin Seoub; Park, Na Ri; Nam, Heechul; Sung, Pil Soo; Bae, Si Hyun; Choi, Jong Young; Yoon, Seung Kew; Hur, Wonhee; Jang, Jeong Won (Frontiers in Oncology, 2021)
Background & Aims Cancer metastasis is responsible for the majority of cancer-related deaths. Exosomal miRNAs have emerged as promising biomarkers for cancer, serving as signaling molecules that can regulate tumor growth and metastasis. This study examined circulating exosomal miRNAs that could predict hepatocellular carcinoma (HCC) metastasis. Methods Exosomal miRNA was measured by quantitative real-time PCR (qRT-PCR) in a large set of patients (n = 284). To investigate the role of exosomal miRNA in HCC, we performed a series of in vitro tests, such as exosome labeling, qRT-PCR, reverse transcription PCR, wound healing assay, transwell assay, and Western blot assay. Results Exosomal miR-125b was drastically downregulated in HCC patients with metastasis than in those without metastasis. In vitro, we observed the uptake of miR-125b by exosome in recipient cells. Exosome-mediated miR-125b significantly inhibited migration and invasion abilities and downregulated the mRNA expressions of MMP-2, MMP-9, and MMP-14 in recipient cells via intercellular communication. Further investigation revealed that miR-125b suppressed SMAD2 protein expression in recipient cells by binding to its 3′ untranslated regions. Exosome-mediated miR-125b transfer also disrupted TGF-β1–induced epithelial–mesenchymal transition and TGF-β1/SMAD signaling pathway in recipient cells by leading to a decrease of SMAD2 protein expression. Moreover, exosomal miR-125b was downregulated after metastasis compared with that at baseline in patients with serial measurements before and after metastasis. Conclusions The results imply that exosome-mediated miR-125b exerts anti-metastatic properties in HCC. These findings highlight that circulating exosomal miR-125b might represent a reliable biomarker with diagnostic and therapeutic implications for extrahepatic metastasis from HCC.